Electrolytic capacitor and manufacturing method
By using an electrolytic capacitor with a valve-acting metal substrate, a sintered layer, an anode sintered body, a cathode body, and an electrolyte containing specific amines, the issue of capacitance degradation in high-temperature environments is addressed, achieving stable capacitance retention and low leakage current.
Patent Information
- Application Number
- JP2024165519
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-28
- Filing Date
- 2024-09-24
- Publication Date
- 2025-04-09
AI Technical Summary
Electrolytic capacitors with anode sintered bodies made of valve metal powder sintered experience significant capacity degradation when exposed to high temperatures, outperforming capacitors with etched anode foils.
The electrolytic capacitor incorporates a valve-acting metal substrate with a sintered layer of valve-acting metal powder, an anode sintered body with a dielectric film, a cathode body, and an electrolyte containing secondary amines, tertiary amines, or both as base components, which are used to form a stable dielectric film and maintain capacitance under high temperature conditions.
This configuration effectively suppresses the deterioration of capacitance in electrolytic capacitors even when exposed to high temperatures, maintaining a high capacitance retention rate and minimizing leakage current.
Smart Images

Figure 2025059023000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolytic capacitor having a sintered anode and a manufacturing method thereof. [Background technology]
[0002] An electrolytic capacitor has anodes and cathodes made of valve metals such as tantalum or aluminum. The anodes are enlarged by forming the valve metal into a sintered body or an etched foil, and the enlarged surface is coated with a dielectric film by anodizing or other treatment. An electrolyte is interposed between the anodes and cathodes. The electrolyte is in close contact with the uneven surface of the anode, and functions as a true cathode.
[0003] The electrolytic capacitor can increase the specific surface area by enlarging the surface of the anode body, and therefore has a large capacitance, which meets the demand for higher capacity. In addition, the contact area of the electrolyte with the dielectric film of the anode body increases, making it easier to further increase the capacitance of the electrolytic capacitor.
[0004] In order to miniaturize or increase the capacity of an electrolytic capacitor, it is important to improve the capacitance per unit volume. The capacitance of an electrolytic capacitor is proportional to the surface area of the dielectric film. Therefore, a surface enlargement process is performed by etching, and etching pits tend to extend from the surface of the electrode foil to a deeper portion. In other words, in electrolytic capacitors, the core of the anode body tends to become thinner. Therefore, the anode body is easily fragile, and when it is wound, it is bent in places.
[0005] If the anode body is bent in places, the capacitor element will become larger. Or, if the anode body is bent in places, the capacitance per unit volume will decrease. Otherwise, the anode body will be treated as a defective product, and the yield will decrease.
[0006] In view of this, a method of increasing the surface area by forming an anode sintered body having a sintered layer of a valve metal has been studied (see, for example, Patent Document 1). The sintered body has a porous structure in which the valve metal powder particles maintain voids between each other. This increases the surface area of the anode body. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 7168823 Summary of the Invention [Problem to be solved by the invention]
[0008] It has been confirmed that, when exposed to a high-temperature environment, an electrolytic capacitor having an anode sintered body made of sintered valve metal powder exhibits greater capacity degradation over time than an electrolytic capacitor having an etched anode foil.
[0009] The present invention has been proposed to solve the above-mentioned problems, and its object is to provide an electrolytic capacitor that has an anode sintered body and that exhibits little degradation in capacitance even when exposed to high temperatures, and a manufacturing method thereof. [Means for solving the problem]
[0010] In order to solve the above problems, the electrolytic capacitor of this embodiment comprises an anode sintered body having a valve metal base material, a sintered layer formed by sintering valve metal powder onto the surface of the valve metal base material, and a dielectric coating formed on the sintered layer, a cathode body facing the anode sintered body, and an electrolyte solution containing a secondary amine, a tertiary amine, or both, as a base component.
[0011] The electrolytic solution may contain a base component, and the secondary amine, the tertiary amine, or both may be contained in an amount of 25 mol % or more based on the total amount of the base component.
[0012] The secondary amine and the tertiary amine may be dimethylamine, diethylamine, trimethylamine, triethylamine or ethyldimethylamine.
[0013] The electrolyte may contain a solvent of a glycol compound.
[0014] The anode sintered body may have a dividing portion that divides the sintered layer.
[0015] The electrolyte may contain 24 mmol or more and 63 mmol or less of a base component per 100 g of the electrolyte.
[0016] In order to solve the above-mentioned problems, the manufacturing method of the electrolytic capacitor of the present embodiment includes an anode formation step of forming an anode sintered body having a sintered layer by sintering valve metal powder onto a valve metal base, a chemical conversion step of forming a dielectric film on a surface layer of the sintered layer, an element formation step of forming a capacitor element in which the anode sintered body and a cathode body face each other via a separator, and an impregnation step of impregnating the capacitor element with an electrolytic solution containing a secondary amine, a tertiary amine, or both.
[0017] The anode forming step further includes a step of dividing the sintered layer. Effect of the Invention
[0018] According to the present invention, the electrolytic capacitor is provided with an anode sintered body, and degradation of the capacitance is suppressed even when exposed to high temperatures. [Brief description of the drawings]
[0019] [Figure 1] 1 is a graph showing the relationship between amine series number and capacitance retention rate. [Diagram 2] 1 is a graph showing the relationship between the content of diethylamine in all cations and the retention rate of capacitance. [Diagram 3] 1 is a graph showing the relationship between the content of diethylamine in all cations and leakage current. [Figure 4] 1 is a graph showing the relationship between the content of cations per 100 g of electrolyte and the retention rate of capacitance when the only cation is diethylamine. [Diagram 5] 1 is a graph showing the relationship between the cation content per 100 g of electrolyte and the capacitance retention rate when 25 wt % of the cations is diethylamine. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, a solid electrolytic capacitor according to an embodiment will be described, however, the present invention is not limited to the embodiment described below.
[0021] (Electrolytic capacitor) The electrolytic capacitor includes a capacitor element. The capacitor element includes a sintered anode body, a cathode body, and an electrolyte. A dielectric film is formed on the surface of the sintered anode body. The sintered anode body and the cathode body face each other with a separator interposed therebetween. The electrolyte is impregnated into the sintered anode body and the separator, and is interposed between the dielectric film of the sintered anode body and the cathode body, and is in close contact with the dielectric film of the sintered anode body to function as a true cathode.
[0022] This capacitor element is a wound type. In the wound type, the anode sintered body and the cathode body are wound with a separator sandwiched between them. An anode lead is connected to the anode sintered body, and a cathode lead is connected to the cathode body, and these are drawn out from the end faces of the capacitor element. The anode lead and the cathode lead are electrically and mechanically connected to the anode sintered body and the cathode body by cold welding, ultrasonic welding, stitch connection, laser welding, or the like.
[0023] The capacitor element is housed in an exterior case that has one end closed and the other end open, and the capacitor element is sealed in the exterior case with a sealing body. The sealing body is an elastic insulator such as a rubber plate, or a laminate of a hard substrate insulating plate such as a synthetic resin plate and an elastic insulator, which is crimped from the outside of the exterior case. A pressure valve that opens when the pressure inside the case exceeds a predetermined value may be formed at the bottom of the case. After the capacitor element is sealed in the exterior case, the electrolytic capacitor is subjected to an aging process to complete the production. In the aging process, a direct current voltage is applied to the electrolytic capacitor to repair defects in the dielectric film layer, etc.
[0024] The electrolytic capacitor is electrically connected to the mounted circuit via the anode lead and cathode lead. By being electrically connected to the mounted circuit, the solid electrolytic capacitor becomes a passive element that obtains capacitance due to the dielectric polarization of the dielectric film and stores and discharges electric charge.
[0025] (sintered anode) The anode sintered body is a foil made of a valve metal, for example, an anode foil. The anode sintered body is produced by attaching a valve metal powder to the surface of a base foil made of an elongated valve metal, sintering the powder, and forming a sintered layer. In a wound electrolytic capacitor, the anode sintered body has a long strip shape. The valve metal is aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth, antimony, etc. The purity of the valve metal is preferably 99.9% or more for the anode body, and may contain other elements such as silicon, iron, copper, manganese, magnesium, chromium, zinc, titanium, vanadium, gallium, nickel, boron, and zirconium.
[0026] The sintered layer has a porous structure in which valve metal powder is sintered. The sintered layer increases the surface area of the anode body. The sintered layer may have a plurality of dividing portions that divide the sintered layer. The dividing portions are formed by cracking, splitting, notching, or digging into the surface layer of the sintered layer. That is, examples of the dividing portions are cracks, fissures, slits, notches, or digging. The dividing portions extend deep from the surface of the sintered layer toward the core, and generally extend in a direction along the winding axis of the winding.
[0027] Since the sintered layer has a divided section, bending stress is dispersed, so that in the case of a wound electrolytic capacitor, cracks that destroy the base foil are less likely to occur during winding, and smooth, good winding is possible. In addition, the formation of the divided section makes it easier for the electrolyte to penetrate into the sintered layer, i.e., the porous structure, and is thought to improve the capacity retention rate.
[0028] The dielectric film is formed on one or both surfaces of the anode sintered body. The dielectric film is typically an oxide film formed on the surface of the anode sintered body, and if the anode sintered body is made of aluminum, it is an aluminum oxide layer obtained by oxidizing the sintered layer. In the chemical conversion treatment for forming the dielectric film, a voltage is applied to the anode body in the chemical conversion solution so as to achieve a desired withstand voltage. For example, when producing an electrolytic capacitor with a rated voltage of about 450V, the nominal chemical conversion voltage of the anode body is preferably 580Vfs or more. The dividing portion may have a dielectric film.
[0029] (cathode body) In the case of a wound-type electrolytic capacitor, the cathode body is preferably a foil made of a valve metal and stretched. This foil is called a cathode foil. The purity of the cathode body is preferably 99% or more. A surface expansion layer is formed on the cathode body. A plain foil without a surface expansion layer may be used as the cathode body. The cathode body may have a natural oxide film or a thin oxide film of about 1 to 10 Vfs formed by chemical conversion treatment. The natural oxide film is formed by the reaction of the cathode body with oxygen in the air.
[0030] Furthermore, the cathode body may be provided with a conductive layer. The conductive layer is laminated on the cathode foil. The conductive layer may mainly contain an inorganic substance or an inorganic compound. Examples of the inorganic substance or inorganic compound include titanium, zirconium, tantalum, niobium, their nitrides or carbides, aluminum carbide, carbon materials, and composites or mixtures thereof. Specific examples include a carbon layer which is a conductive layer of a carbon material, a conductive layer of titanium nitride, a conductive layer of titanium carbide, a conductive layer in which titanium and a carbon material are mixed, and a conductive layer in which aluminum carbide (Al4C3) and titanium oxide (TiO2) are composited. The conductive layer containing the carbon material, i.e., the carbon layer, contains graphite, carbon black, or a mixture thereof as the carbon material.
[0031] (electrolyte) An electrolyte is a solution in which a solute is added to a solvent. The solute is an organic acid or its salt, an inorganic acid or its salt, or a composite compound of an organic acid and an inorganic acid or its salt, and is an ion-dissociable salt that dissociates into an acid component and a base component. The solvent may be used alone or in combination of two or more kinds.
[0032] The electrolyte contains at least a secondary amine, a tertiary amine, or both as a base component. The electrolyte may contain a plurality of secondary amines, and may contain a plurality of tertiary amines. Examples of the secondary amine include dimethylamine, diethylamine, ethylmethylamine, and dibutylamine. Examples of the tertiary amine include trimethylamine, triethylamine, tributylamine, ethyldimethylamine, and ethyldiisopropylamine.
[0033] As long as the base component includes a secondary amine, a tertiary amine, or both, the electrolyte may further include other types of base components. Examples of other types of base components include ammonia, quaternary ammonium, quaternized amidinium, primary amine, sodium, potassium, etc. Examples of quaternary ammonium include tetramethylammonium, triethylmethylammonium, tetraethylammonium, etc. Examples of quaternized amidinium include ethyldimethylimidazolinium, tetramethylimidazolinium, etc. Examples of primary amine include methylamine, ethylamine, propylamine, etc.
[0034] By including a secondary amine, a tertiary amine, or both as a base component in the electrolyte, the capacitance of an electrolytic capacitor having an anode sintered body formed by sintering a valve metal powder is prevented from deteriorating even when exposed to a high-temperature environment. In particular, the content of the secondary amine, the content of the tertiary amine, or the total content of both is preferably 25 mol% or more based on the total content of the base components in the electrolyte. When the content is 25 mol% or more, the degradation of the capacitance is particularly effectively prevented even when the electrolytic capacitor is exposed to a high-temperature environment. Furthermore, when the content is 25 mol% or more, leakage current is suppressed even when the electrolytic capacitor is exposed to a high-temperature environment.
[0035] The total amount of base components contained in the electrolyte is preferably in the range of 24 mmol or more and 63 mmol or less per 100 g of electrolyte. If the total amount of base components contained in the electrolyte is within this range, the capacitance of the electrolytic capacitor is not significantly deteriorated even if the electrolytic capacitor is exposed to a high temperature environment. That is, the capacitance of the electrolytic capacitor after being exposed to a high temperature environment is not significantly decreased and is maintained high, compared to the capacitance of an electrolytic capacitor that has not been exposed to high temperatures.
[0036] Examples of organic acids that can be used as acid components include carboxylic acids such as oxalic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, adipic acid, benzoic acid, toluic acid, enanthic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, resorcylic acid, phloroglucinic acid, gallic acid, gentisic acid, protocatechuic acid, pyrocatechuic acid, trimellitic acid, and pyromellitic acid, as well as phenols and sulfonic acids. Examples of inorganic acids include boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid. Examples of composite compounds of organic acids and inorganic acids include borodisalicylic acid, borodioxalic acid, borodiglycolic acid, borodimalonic acid, borodisuccinic acid, borodiadipic acid, borodiazelaic acid, borodibenzoic acid, borodimaleic acid, borodilactic acid, borodimalic acid, boroditartaric acid, borodicitric acid, borodiphthalic acid, borodi(2-hydroxy)isobutyric acid, borodiresorcylic acid, borodimethylsalicylic acid, borodinaphthoic acid, borodimandelic acid, and borodi(3-hydroxy)propionic acid.
[0037] The solvent may be either a protic polar solvent or an aprotic polar solvent. Representative examples of the protic polar solvent include monohydric alcohols, polyhydric alcohols, and oxyalcohol compounds. Representative examples of the aprotic polar solvent include sulfones, amides, lactones, and cyclic amides.
[0038] Examples of monohydric alcohols include ethanol, propanol, butanol, pentanol, hexanol, cyclobutanol, cyclopentanol, cyclohexanol, benzyl alcohol, etc. Examples of polyhydric alcohols and oxyalcohol compounds include ethylene glycol, propylene glycol, glycerin, methyl cellosolve, ethyl cellosolve, methoxypropylene glycol, dimethoxypropanol, etc.
[0039] Examples of sulfones include dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, sulfolane, 3-methyl sulfolane, and 2,4-dimethyl sulfolane. Examples of amides include N-methylformamide, N,N-dimethylformamide, N-ethylformamide, N,N-diethylformamide, N-methylacetamide, N,N-dimethylacetamide, N-ethylacetamide, N,N-diethylacetamide, and hexamethylphosphoric amide. Examples of lactones and cyclic amides include γ-butyrolactone, γ-valerolactone, δ-valerolactone, N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butylene carbonate, and isobutylene carbonate.
[0040] As the solvent of the electrolytic solution, a glycol compound is preferred. The glycol compound is a compound having a structure in which hydrogen atoms bonded to two carbon atoms of an aliphatic hydrocarbon having two or more carbon atoms or a cyclic aliphatic hydrocarbon are replaced by hydroxyl groups one by one. The glycol compound has a high boiling point of 150°C or more. This glycol compound improves the chemical conversion property of the dielectric film, and can reduce the ESR of the electrolytic capacitor and improve the voltage resistance. Examples of the glycol compound include ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, and polyoxyethylene glycol. The electrolytic solution may contain one type of glycol compound solvent, or two or more types of glycol compound solvents. Furthermore, as the solvent, a glycol compound may be used alone, or a glycol compound may be combined with another type.
[0041] In addition, examples of additives include complex compounds of boric acid and polysaccharides (mannitol, sorbitol, etc.), complex compounds of boric acid and polyhydric alcohols, boric acid esters, nitro compounds, phosphate esters, colloidal silica, etc. These may be used alone or in combination of two or more. The nitro compounds act as gas absorbents and suppress the generation of hydrogen gas in the electrolytic capacitor. Examples of nitro compounds include o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenol, m-nitrophenol, p-nitrophenol, o-nitrobenzyl alcohol, m-nitrobenzyl alcohol, p-nitrobenzyl alcohol, o-nitroacetophenone, m-nitroacetophenone, p-nitroacetophenone, etc. Examples of pressure resistance improvers include polyethylene glycol, polypropylene glycol, and polyoxyethylene glycerin.
[0042] (Separator) The separator may be made of cellulose such as kraft, Manila hemp, esparto, hemp, rayon, or the like, or mixed papers thereof; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof; polytetrafluoroethylene-based resins, polyvinylidene fluoride-based resins, vinylon-based resins, polyamide-based resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide-based resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, and polyvinyl alcohol resins; and the like, and these resins may be used alone or in combination.
[0043] The separator may be fibrillated by generating thin fibers that branch out from the surface of the original fibers, such as fibrillated cellulose. The fibrillation can be achieved, for example, by beating. The fibrillated fibers are entangled with each other using the fibrillated thin fibers, improving the strength of the separator. This allows the separator to be made thinner. The thinner separator allows the anode sintered body and cathode body per unit volume to be made longer and larger, improving the capacitance of the electrolytic capacitor.
[0044] (Manufacturing method) An example of a manufacturing method for a wound electrolytic capacitor is as follows. First, in the anode formation process, a sintered anode body is formed by sintering a valve metal powder. In the chemical conversion process, a dielectric film is formed on the sintered anode body. An anode lead and a cathode lead are electrically and mechanically connected to the sintered anode body and the cathode body.
[0045] In the element formation process, a long anode sintered body and a cathode body are wound with a separator interposed therebetween to produce a cylindrical wound body. The separator is overlapped so that one end of the separator protrudes beyond one end of the anode sintered body and the cathode body. The protruding separator is wound first so that the core of the wound body is aligned with the short sides of the anode sintered body and the cathode body to produce a winding core. Then, the winding core is used as a winding shaft to roll the long sides of the anode sintered body and the cathode body.
[0046] After the winding, a repair chemical conversion process may be provided to repair bare metal portions of the valve action metal exposed when the anode sintered body and the cathode body are cut to a desired width, and to repair defects in the anode sintered body and the cathode body caused by physical stress such as winding.
[0047] In the repair anodization step, the wound body is immersed in anodization liquid and a voltage is applied. As the anodization liquid, a phosphoric acid-based anodization liquid such as ammonium dihydrogen phosphate, a boric acid-based anodization liquid such as ammonium borate, an adipic acid-based anodization liquid such as ammonium adipate, or an anodization liquid in which boric acid and a dicarboxylic acid such as citric acid are mixed is used. For example, the voltage is preferably set to a value of 0.1 to 1.2 times the anodization voltage. In addition, as a method of applying a voltage during repair anodization, a method of applying a constant voltage from the start of repair anodization, or a method of increasing the applied voltage stepwise at regular intervals, etc., are appropriately selected.
[0048] In the impregnation step, the capacitor element is immersed in the electrolyte, and the electrolyte is impregnated into the voids in the capacitor element. In order to impregnate the electrolyte into finer voids, a pressure reduction treatment or a pressure increase treatment may be performed as necessary. The electrolyte impregnation step may be repeated multiple times. For example, the inside of the capacitor element may be reduced in pressure, and the electrolyte may be injected into the inside of the capacitor element while pressurizing the electrolyte. EXAMPLES
[0049] The electrolytic capacitors of the examples will be described in more detail below, but the present invention is not limited to the examples described below.
[0050] (Examples 1 to 5) Electrolytic capacitors were produced in Examples 1 to 5 and Comparative Examples 1 and 2. The anode sintered body used was an anode sintered body in which a dielectric film was formed on a sintered layer made of sintered aluminum grains on an aluminum base material. This sintered layer had a divided portion.
[0051] The cathode body is an aluminum foil with an enlarged surface. The aluminum foil is immersed in an ammonium borate solution at a temperature of 85°C, and a constant current of 2 mA is applied until a voltage of 3 V is reached. Lead wires are connected to the anode sintered body and the cathode body, and the anode sintered body and the cathode body are wound facing each other with a cellulose separator interposed between them.
[0052] The wound body was immersed in an electrolyte, and the electrolyte was impregnated into the gaps in the wound body. The solvent of the electrolyte was a mixed solvent of water and ethylene glycol. The electrolyte contained azelaic acid as a solute of an anion component. In addition, a gas absorbent and a pressure resistance improver were added to the electrolyte as additives. The electrolyte further contained a cationic component, and the electrolytic capacitors of each of the examples and comparative examples had different types of cationic components in the electrolyte. The electrolyte contained equimolar anionic and cationic components, each of which was contained at 24 mmol per 100 g of electrolyte.
[0053] The types and composition ratios (parts by weight) of cations in the electrolyte solutions of the respective Examples and Comparative Examples are as shown in Table 1 below. (Table 1) TIFF2025059023000002.tif131170
[0054] A rubber seal was attached to the open end of the bottomed cylindrical exterior case housing the capacitor element impregnated with the electrolyte, and the case was then crimped to seal it. Each electrolytic capacitor was aged by applying a voltage. The capacitor element was 10 mm in diameter, 20 mm in height, and had a rated voltage of 450 V.
[0055] (Capacitance test) The electrolytic capacitors of Examples 1 to 5 and Comparative Examples 1 and 2 were left in a temperature environment of 150°C for 300 hours. The capacitance was measured before and after leaving the capacitor in the high-temperature environment, and the retention rate of the capacitance after leaving the capacitor in the high-temperature environment was calculated as a percentage. The retention rate of the capacitance was calculated as a percentage by dividing the capacitance after leaving the capacitor in the high-temperature environment by the capacitance before leaving the capacitor in the high-temperature environment. The capacitance was measured using an LCR meter (Agilent ZM2376, manufactured by NF Corporation). The ambient temperature during the measurement was 20°C, the DC bias was 1.5V, the signal level was a sine wave of 1.0Vrms, and the measurement frequency was 120Hz.
[0056] The results of the capacitance retention rate are shown in Table 2 below. Table 2 shows the cation species as the type of cation. (Table 2) TIFF2025059023000003.tif91156
[0057] In addition, based on the results of Examples 1 to 5 and Comparative Examples 1 and 2 in Table 2 above, a graph showing the relationship between the amine series and the capacitance retention rate was created as shown in FIG. 1. In the figure, the NH3 plot is the retention rate of Comparative Example 1 in which ammonia was contained. The MA plot is the retention rate of Comparative Example 2 in which methylamine was contained. The DMA plot is the retention rate of Example 1 in which dimethylamine was contained. The DEA plot is the retention rate of Example 2 in which diethylamine was contained. The TMA plot is the retention rate of Example 3 in which trimethylamine was contained. The EDMA plot is the retention rate of Example 4 in which ethyldimethylamine was contained. The TEA plot is the retention rate of Example 5 in which triethylamine was contained.
[0058] As shown in Table 2 and Figure 1, Examples 1 and 2, which contain secondary amines dimethylamine or diethylamine, and Examples 3 to 5, which contain tertiary amines trimethylamine, ethyldimethylamine, or triethylamine, have higher capacitance retention rates than Comparative Examples 1 and 2, which contain ammonia or a primary amine. That is, it was confirmed that in an electrolytic capacitor having an anode sintered body, when the electrolyte contains a secondary amine, a tertiary amine, or both, the capacitance degradation when exposed to a high temperature environment is suppressed. However, it was also confirmed that, even if the electrolyte is the same amine system, when a primary amine is contained, the capacitance degradation is rather large.
[0059] (Examples 6-8) Furthermore, electrolytic capacitors of Examples 6 to 8 were produced. The electrolytic capacitors of Examples 6 to 8 were produced by the same manufacturing method and under the same conditions as Examples 1 to 5, except for the composition of the electrolytic solution, and had the same configuration and anode sintered body. The electrolytic solutions of Examples 6 to 8 contained ammonia in addition to diethylamine, which is a secondary amine. In Examples 6 to 8, the amount of diethylamine added was changed so that the molar percentage of diethylamine relative to the total number of moles of the cationic components, diethylamine and ammonia, was different, being 25 mol%, 50 mol%, and 75 mol%.
[0060] The types and composition ratios (parts by weight) of cations in the electrolyte solutions of Examples 6 to 8, and the molar percentage of diethylamine relative to the total cationic components are as shown in Table 3. Table 3 also shows Comparative Example 1 and Example 2. (Table 3) TIFF2025059023000004.tif103161
[0061] (Capacitance test) The electrolytic capacitors of Examples 2, 6 to 8 and Comparative Example 1 were left in a temperature environment of 150°C for 307 hours. The capacitance was measured before and after leaving in the high temperature environment, and the retention rate of the capacitance after leaving in the high temperature environment was calculated as a percentage. The method and conditions for measuring the capacitance were the same as those of Example 1.
[0062] The capacitance retention results are shown in Table 4 below. (Table 4) TIFF2025059023000005.tif71156
[0063] In addition, based on the results of Examples 2, 6 to 8 and Comparative Example 1 in Table 4 above, a graph was created showing the relationship between the diethylamine content in all cations and the capacitance retention rate, as shown in FIG. 2.
[0064] As shown in Table 4 and Figure 2, it was confirmed that when 25 wt% or more of diethylamine is contained in the total cations including ammonia and diethylamine, the electrolytic capacitor can maintain a better capacitance even when exposed to a high-temperature environment. That is, it was confirmed that in an electrolytic capacitor having an anode sintered body, when the electrolyte contains 25 wt% or more of secondary amine, tertiary amine, or both, relative to the total cations, the degradation of the capacitance when exposed to a high-temperature environment is further suppressed.
[0065] (Leakage current test) The electrolytic capacitors of Examples 2, 6 to 8, and Comparative Example 1 were left in a temperature environment of 150°C for 90 hours. The leakage current was measured before and after leaving the capacitors in the high-temperature environment. The leakage current was measured 5 minutes after applying 450V in a temperature environment of 20°C.
[0066] The leakage current measurement results are shown in Table 5 below. (Table 5) TIFF2025059023000006.tif71156
[0067] In addition, based on the results of Examples 2, 6 to 8, and Comparative Example 1 in Table 5 above, a graph was created showing the relationship between the diethylamine content in all cations and the leakage current after exposure to a high-temperature environment, as shown in FIG. 3.
[0068] As shown in Table 5 and Figure 3, it was confirmed that if 25 wt% or more of diethylamine is contained in the total cations, including ammonia and diethylamine, the leakage current can be suppressed even when the electrolytic capacitor is exposed to a high-temperature environment. That is, in an electrolytic capacitor having an anode sintered body, it was confirmed that if the electrolyte contains 25 wt% or more of secondary amine, tertiary amine, or both, relative to the total cations, the leakage current when exposed to a high-temperature environment can be suppressed to a low level.
[0069] (Examples 9-18) Furthermore, electrolytic capacitors of Examples 9 to 18 were produced. The electrolytic capacitors of Examples 9 to 14 were produced by the same method and under the same conditions as Example 2, except for the total amount of all cations in the electrolyte, and had the same configuration. The electrolytic capacitors of Examples 15 to 18 were produced by the same method and under the same conditions as Example 6, except for the total amount of all cations in the electrolyte, and had the same configuration.
[0070] The cation in the electrolyte of Example 2 and Examples 9 to 14 is only diethylamine, which is a secondary amine. In Example 2 and Examples 9 to 14, the amount of diethylamine added to the electrolyte is changed in the range of 5.2 mmol to 62.8 mmol per 100 g of electrolyte.
[0071] The composition ratios (parts by weight) of the electrolyte solutions of Examples 2 and 9 to 14 and the diethylamine content per 100 g of the electrolyte solution are as shown in Table 6 below. (Table 6) TIFF2025059023000007.tif97161
[0072] The cations in the electrolytes of Example 6 and Examples 15 to 18 are diethylamine and ammonia, which are secondary amines. Diethylamine accounts for 25 mol% of the total cations, including ammonia and diethylamine. In Example 6 and Examples 15 to 18, the total amount of cations in the electrolytes, including ammonia and diethylamine, is changed in the range of 17.3 mmol to 52.5 mmol per 100 g of electrolyte.
[0073] The composition ratios (parts by weight) of the electrolyte solutions of Example 2 and Examples 15 to 18 and the diethylamine content per 100 g of the electrolyte solution are as shown in Table 7 below. (Table 7) TIFF2025059023000008.tif107161
[0074] (Capacitance test) The electrolytic capacitors of Examples 2 and 6 and Examples 9 to 18 were left in a temperature environment of 150° C. for 307 hours. The capacitance was measured before and after leaving in the high-temperature environment, and the retention rate of the capacitance after leaving in the high-temperature environment was calculated as a percentage. The method and conditions for measuring the capacitance were the same as those of Example 1.
[0075] The results of the capacitance retention rates of Example 2 and Examples 9 to 14 are shown in Table 8 below. (Table 8) TIFF2025059023000009.tif91156
[0076] The results of the capacitance retention rates of Example 6 and Examples 15 to 18 are shown in Table 9 below. (Table 9) TIFF2025059023000010.tif71156
[0077] In addition, based on the results of Examples 2 and 9 to 14 and Table 8 above, a graph showing the relationship between the cation content per 100 g of electrolyte and the capacitance retention rate was created as shown in Figure 4. Based on the results of Examples 6 and 15 to 18 and Table 9 above, a graph showing the relationship between the cation content per 100 g of electrolyte and the capacitance retention rate was created as shown in Figure 5.
[0078] As shown in Table 8 and Figure 4, the capacitance retention rates of the electrolytic capacitors of Examples 2 and 11 to 14 are much higher than those of Examples 9 and 10. In addition, as shown in Table 9 and Figure 5, the capacitance retention rates of the electrolytic capacitors of Examples 6 and 16 to 18 are much higher than those of Example 15.
[0079] That is, it was confirmed that when the total content of cations in the electrolyte is 24 mmol or more per 100 g of electrolyte, the retention rate of the capacitance of the electrolytic capacitor is much higher than when the total content is less than 24 mmol. Also, Examples 2 and 9 to 14, which contain only diethylamine, and Examples 6 and 15 to 18, in which diethylamine is 25 mol% of the total cations, have the same tendency, and it was confirmed that when the total content of cations in the electrolyte is 24 mmol or more per 100 g of electrolyte, the retention rate of the capacitance of the electrolytic capacitor is much higher than when the total content is less than 24 mmol.
[0080] Furthermore, when the total content of cations in the electrolyte is in the range of up to 63 mmol per 100 g of electrolyte, no significant fluctuation is observed in the capacitance retention rate of the electrolytic capacitor.
[0081] It was confirmed that the capacitance retention rate of an electrolytic capacitor can be further increased by providing an anode sintered body, containing a secondary amine, a tertiary amine or both as a base component in an electrolyte, and setting the content of the base component in the electrolyte to 24 mmol or more and 63 mmol or less per 100 g of electrolyte.
Claims
1. an anode sintered body having a valve metal base material, a sintered layer formed by sintering a valve metal powder onto the surface of the valve metal base material, and a dielectric coating formed on the sintered layer; a cathode body facing the anode sintered body; an electrolyte solution containing a secondary amine, a tertiary amine, or both as a base component; To have An electrolytic capacitor characterized by:
2. The electrolyte solution is the secondary amine, the tertiary amine, or both of them are contained in an amount of 25 mol % or more based on the total amount of the base component; 2. The electrolytic capacitor according to claim 1 .
3. the secondary amine and the tertiary amine are dimethylamine, diethylamine, trimethylamine, triethylamine or ethyldimethylamine; 3. The electrolytic capacitor according to claim 1 or 2,
4. The electrolyte contains a solvent for a glycol compound; 3. The electrolytic capacitor according to claim 1 or 2,
5. the anode sintered body has a dividing portion dividing a sintered layer; 3. The electrolytic capacitor according to claim 1 or 2,
6. The electrolyte contains a base component in an amount of 24 mmol or more and 63 mmol or less per 100 g of the electrolyte; 3. The electrolytic capacitor according to claim 1 or 2,
7. an anode forming step of sintering a valve metal powder onto a valve metal base to form an anode sintered body having the sintered layer; a chemical conversion step of forming a dielectric film on a surface layer of the sintered layer; an element forming step of forming a capacitor element in which the anode sintered body and a cathode body face each other via a separator; an impregnation step of impregnating the capacitor element with an electrolyte solution containing a secondary amine, a tertiary amine, or both; containing, A method for manufacturing an electrolytic capacitor comprising the steps of:
8. the anode forming step further includes a step of dividing the sintered layer; The method for producing an electrolytic capacitor according to claim 7,
Citation Information
Patent Citations
electrolytic capacitor
JP7168823B1
Cited By
Electrolytic capacitor
WO2026063155A1